Turkey : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Financial System Stability Assessment on Turkey discusses macroeconomic development and trend in the financial system. The financial system does not appear to face major immediate threats, but vulnerabilities remain. Turkey remains dependent on capital inflows and thus on international investor sentiment. Large holdings of public sector debt by banks makes their solvency, profitability, and liquidity highly sensitive to adverse market revaluation of these securities in the event of external shocks or/and internal political uncertainties.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Turkey